Delivery of bone marrow mesenchymal stem cell-derived exosomes into fibroblasts attenuates intestinal fibrosis by weakening its transdifferentiation via the CCN2-TGF-β axis - Fangmei Ling; Wenkai Yang; Meng Yuan; Yidong Chen; Junrong Li; Jinhua Wu; Liangru Zhu (Scientific Reports)
Abstract Intestinal fibrosis represents a clinically intractable complication in colitis management. This study elucidates the regulatory mechanisms by which bone mesenchymal stem cell-derived exosomes (BMSC-Exo) modulate the myofibroblastic transdifferentiation of intestinal fibroblast. BMSC-Exo was isolated and characterized. RNA sequencing was performed on TGF-β-activated CCD-18Co fibroblasts following BMSC-Exo intervention. Histopathology, immunoblotting, migration assays, and imaging techniques (immunofluorescence/immunohistochemistry) were employed to quantify extracellular matrix (ECM) deposition and fibrotic responses in both in vitro and murine models. Human colonic specimens from Crohn’s disease (CD) patients with structuring complications were analyzed for fibrotic components. BMSC-Exo was successfully isolated. BMSC-Exo treatment significantly attenuated fibroblast activation and migratory capacity, concomitant with downregulating collagen I and N-cadherin expression. In vivo, histological fibrosis score, collagen deposition, and α-SMA expression were significantly decreased after BMSC-Exo administration. Transcriptomic profiling revealed significant enrichment of ECM remodeling pathways following BMSC-Exo intervention, with connective tissue growth factor (CCN2) identified as a pivotal mediator. Functional validation through CCN2 overexpression demonstrated the mechanistic dependence of BMSC-Exo’s anti-fibrotic effects on the CCN2-TGF-β axis. Clinical specimens revealed a marked increase in collagen fiber deposition and co-upregulation of CCN2 in stenotic CD tissues compared to non-strictured regions. BMSC-Exo exerts potent anti-fibrotic effects through the suppression of fibroblast differentiation, mediated by targeted inhibition of the CCN2-TGF-β signaling nexus. These findings establish exosome-based therapy as a novel therapeutic strategy for intestinal fibrosis.